Self-motivation boost through social media apps: a Gen-Z necessity / Nurliyana Kamilah Khairul Anuar, Farah Hazween Amanah and Muhammad Azril Izuan Ramlan - Khairul Anuar, Nurliyana Kamilah; Amanah, Farah Hazween; Ramlan, Muhammad Azril Izuan (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Gearing up to Industrial Revolution 5.0, the Generation-Z is depending even more on online media with the most utilized social media applications such as TikTok, Instagram, Twitter and the newly in; Threads is no exception. The expeditious advancement of Industrial Revolution 4.0 that was centralized around digitalization has shown a high reliance of the general society towards the internet, mainly the social media applications that were utilized for various life purposes. It eventually changed how we live, work, and communicate. Not only that, it changed the things that we value and the way we value them. Having said that, possessing positive self-motivation is one of the valuable things a person can have. However, with daily news that is filled with Gen-Z experiencing mental health related issues which is quite alarming has strengthened the idea of the need in boosting their self-motivation through an approach that is much closer to them that is the social media application itself.